Methicillin-resistant Staphylococcus aureus in a Secondary Care Hospital in Muzaffarabad, Azad Jammu & Kashmir - Khan, Mumtaz Ahmad (International Journal of Pathology, 2019)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is an important nosocomial and community pathogen. It has a high impact not only on patient morbidity and mortality but also on hospitalization costs.Objective: The objective of this study was to determine the frequency of Methicillin-resistant Staphylococcus aureus (MRSA) in a tertiary care hospital.Methods: This prospective, descriptive study was carried out in the Department of Microbiology, Abbas Institute of Medical Sciences, Muzaffarabad from December 2015 to November 2017. Various clinical specimens for culture & sensitivity testing of both indoor and outdoor patients were received at Pathology Department of Abbas Institute of Medical Sciences. All specimens were inoculated on appropriate media. Staph aureus was identified on the basis of colony morphology, Gram staining, catalase test, coagulase test and DNase test. All confirmed S. aureus isolates were screened for methicillin resistance using cefoxitin (Fox) disk. To check methicillin resistance, bacterial lawn was prepared on Mueller–Hinton agar and Fox disk was placed on it, followed by incubation at 35 °C for 24 hours. Antibiotic sensitivity was interpreted as per the CLSI guidelines.Results: Out of total 261 S. aureus isolates, the frequency of MRSA was 32.18 % (n = 84), While MRSA exhibited 100 % susceptibility to vancomycin and linezolid. Among MRSA, the frequencies of community acquired MRSA and hospital acquired MRSA were 26% (n = 22) and 74 % (n = 62) respectively. The data was analyzed using WHONET software 5.6 versions.Conclusion: We observed considerably high rates of MRSA in a regional hospital. The MRSA is a potential threat to the public health as this can disseminate both in community and indoor patients leading to fatal clinical outcomes. There is an urgent need to improve infection control practices and surveillance program in healthcare settings to limit the spread of such resistant pathogens